2017
DOI: 10.1016/j.ijheatmasstransfer.2017.01.095
|View full text |Cite
|
Sign up to set email alerts
|

Pressure loss and heat transfer performance for additively and conventionally manufactured pin fin arrays

Abstract: Pin fin heat exchangers represent a common, viable means of keeping components cool and are widely used for electronics cooling and turbine airfoil cooling. Advancements in manufacturing technology will allow these heat exchangers to be built using new methods, such as laser powder bed fusion, a form of additive manufacturing. New manufacturing approaches, however, render a direct comparison between newly and conventionally manufactured parts meaningless without a good understanding of the difference in the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(38 citation statements)
references
References 46 publications
3
35
0
Order By: Relevance
“…However, the overall performance is best among all the layout considered. The staggered pin fin layouts both in case b and case c are intermediate in terms of ease of manufacture and performance when compared with case a and case d. The results in the present work are validated with similar work from the literature . Moreover, along with the change in the layout, the inlet velocity of the coolant fluid and axial distance between the pin fins is observed to have a cumulative effect on the microchannel performance, and it is different for different layouts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the overall performance is best among all the layout considered. The staggered pin fin layouts both in case b and case c are intermediate in terms of ease of manufacture and performance when compared with case a and case d. The results in the present work are validated with similar work from the literature . Moreover, along with the change in the layout, the inlet velocity of the coolant fluid and axial distance between the pin fins is observed to have a cumulative effect on the microchannel performance, and it is different for different layouts.…”
Section: Resultsmentioning
confidence: 99%
“…Tang et al numerically investigated the influence of inlet/outlet positions and header forms on the flow and thermal performance of microchannel heat sinks and found that the performance of I‐type inlet‐outlet with a rectangular header is better compared with other cases. Kirsch and Thol investigated the microchannel pin fin arrays manufactured using Laser Powder Bed Fusion to study their pressure drop and heat transfer characteristics. The effect of pin fin geometry was numerically analyzed by Jadhav et al in terms of the Nusselt number and pressure drop and observed that the elliptical pin fins experience minimum pressure drop.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed the validity of the regression model and the effectivity of the optimal parameters. An experimental investigation on heat transfer performance and pressure drop of conventionally and additively fabricated pin‐fin arrays was performed by Kirsch and Thole 19 . When rough and smooth fin surfaces were compared, it showed that the rough surface highly affects the friction factor as well as augments heat transfer rather than smooth pin‐fin arrays.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Therefore, a bi-exponential adjustment of the experimental data was done to obtain the analytical form of the liquid height, in a similar way to [29], with a view to the performance of further comparative capillary tests. This adjustment predicted values within the ±5% threshold.…”
Section: It Consists Ofmentioning
confidence: 99%